Towards an open conservation documentation service. Issue 1 (2nd January 2021) - Velios, Athanasios
Abstract: This article proposes the implementation of a system which allows for sharing conservation data using Linked Data technologies. It begins with a review of the reasons why conservation data should be shared by default and highlights the value of sharing for practical tasks such as assessing environmental control based on condition surveys and environmental monitoring records. The article also makes the argument for public delivery of work which is completed with public funding and continues by examining the value of sharing data in other fields of research. It makes reference to important projects which were only possible because of sharing data, such as the Human Genome Project (HGP) and other projects in the fields of meteorology and biodiversity. A short introduction to '5 Star Linked Data' is included alongside a description of key concepts for Linked Data, such as the production and maintenance of Uniform Resource Identifiers (URIs). An outline of the proposed work for making conservation data sharable is given which includes terminology harmonisation, reconciliation of records and mapping of local databases to a global schema (CIDOC-CRM). The article concludes with an attempt to identify ongoing costs for the community to maintain a data sharing system and refers to standard subscription models of conservation professional bodies and the requirement for synergy across them.